Entretien avec Joane Hétu - Arroyas, Frédérique (Critical Studies in Improvisation / Études critiques en improvisation, 2005)

Y a-t-il des créatrices en musique au Québec ? - Carignan, Nicole; Leblanc (FAMEQ à la une, 2005)

Rufus Wainwright - De Curtis, Anthony (In Other Words: Artists Talk About Life and Work, 2005)

Constructions of Identity in the Life Stories of Emma Albani and Glenn Gould - Elliott, Robin (Journal of Canadian Studies, 2005)
Biographical accounts of musicians have enjoyed widespread popularity since the late-Victorian era. Literary theory has recently held biography to be a literary construct, rather than a factual enterprise. Biographies and music are both governed by narrative structures and help to create a sense of individual and collective/national identity. Biographical accounts of two Canadian musicians—Emma Albani and Glenn Gould—are examined. Both musicians are Canadian national icons, but there are several problematic issues in their life stories: Albani’s elitism, class consciousness, and ambiguous relationship to Canada, and Gould’s eccentricity and uncertain sexual identity. The article examines how these issues have been handled in various auto/biographical accounts of the two musicians.

Chantal Dumas: a passion for listening and for studio art - Fenner, Victoria (Musicworks, 2005)

The Loudspeaker as Instrument: the soundworks of Nancy Tobin - Friz, Ann (Musicworks, 2005)

Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer

Radical Queers: A Pop Culture Assessment of Montréal's Anti-Capitalist Ass Pirates, the Panthères roses, and Lesbians on Ecstasy - Hogan, Mélanie (Canadian Woman Studies, 2005)
Cet article nous explique comment des artistes montréalaises queer radicales, Anti-Capitalists Ass Pirates, les Panthères roses et Lesbians on Ecstasy, ont transformé la sphère publique en intégrant politique et célébrations dans leurs importants messages à la population.

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)

L’art de chanter… au féminin : de la prise de paroles au jeu de références postmodernes - Oberhuber, Andrea (L’accès des femmes à l’expression musicale. Apprentissage, création, interprétation : les musiciennes dans la cité, 2005)